DIPG-49. BRAINSTEM AND PONTINE VOLUMETRIC ANALYSIS AS A SURROGATE MEASURE OF LOCAL DISEASE CONTROL IN CHILDREN WITH DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (4th December 2020) - Bander, Evan D; Freret, Morgan E; Wembacher-Schroeder, Eva; Wolden, Suzanne L; Souweidane, Mark M
Abstract: INTRODUCTION: Response-assessment in pediatric neuro-oncology (RAPNO) criteria designed to describe treatment outcomes are poorly implemented in diffuse intrinsic pontine glioma (DIPG), due to inter-observer variability in measurement of tumor volume, lack of tumor enhancement, and undefined relationships between radiographic parameters and survival. Given these issues, this study assessed whether anatomically defined brainstem and pontine volumes can serve as surrogate measures of local disease burden and response to therapy in DIPG. METHODS: Thirty-two consecutive patients with newly diagnosed DIPG were treated with standard definitive radiation therapy (RT) between 2010 and 2016 at a single institution. MRI brain scans throughout treatment course were analyzed using iPlan® Flow software (Brainlab AG, Munich, Germany). Semi-automated 3D measurements of the brainstem and pons were calculated using a built-in knowledge-based segmentation approach and manually adjusted. RESULTS: Mean age at diagnosis was 6.5+/-0.5 years (range 2–12 years). Median follow up time was 317 days. Average brainstem volume at diagnosis (Vdiag) was 52.7+/-2.1mL with subsequent decrease at first post-RT MRI to 41.4+/-2.0mL (p < 0.0001). By time of last follow up, brainstem volume increased to 51.9+/-3.3, no longer significantly different as compared to Vdiag (p=0.61). The same relationships were found for pontine volume. CONCLUSIONS: Volumetric changes in the brainstem and pons occur in response to treatment and correlate with local disease burden and response to therapy. This surrogate may be a useful standardized measure in ongoing and future trials involving localized delivery of therapeutics in DIPG that require evaluation of local-regional disease control in addition to survival.